A comparative study of the characteristics of VOx and Y1-xPrxBa2Cu3O7-delta for an uncooled IR detector - Park, CW; Moon, S; Kim, YH; Han, TS; Oh, MW; Chung, HB (KOREAN PHYSICAL SOC, 2001)
We analyzed and compared the characteristics of VOx and Y1-xPrxBa2Cu3O7-delta to find a new material for the IR absorbing layer of a microbolometer. We fabricated VOx thin films by using the RF reactive sputtering method and Y1-xPrxB2Cu3O7-delta pellets with different percents of Pr by using the sintering method. We changed the O-2/Ar ratio and the substrate temperature. The TCR (temperature coefficient of resistance) measurement was carried out to estimate the IR detectivity of the samples. XRD (X-ray diffraction) and EDS (energy distribution spectroscopy) analyses were used to find the characteristics: of the samples. In the case of VOx, the TCR value was about -2 %/K, and in the case of Y1-xPrxBa2Cu3O7-delta, it was about -1.0 %/K.
Keywords: YBACUO THIN-FILMS